Pengembangan Bahan Ajar Flipbook Berbasis Lingkungan pada Mata Pelajaran IPA Kelas V Sekolah Dasar - Saputri, Nabila; Akhbar, M. Taheri; Aryaningrum, Kiki (Indonesian Research Journal on Education, 2023)
This research aims to produce a product of environmental-based flipbook teaching materials in the natural science subject of class V ecosystem material at SD Negeri 20 Pemulutan which has valid and practical results. This study uses research and development research methods (research and development) using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects in this study were 1 media expert validator, 1 material expert validator, 1 linguist validator,and fifth-grade elementary school students in the one-to-one trial with 3 students and 9 students in the small group. The data collection instruments are in the form of validation sheets of teaching materials by validators, practical questionnaires from students, and documentation. Based on the results of the study, the average assessment by media experts was 91.6%; linguists by 83.6%; and material experts at 88.3% with a very valid category, and the results of the student response questionnaires, namely one-to-one by 82.6% and small group field tests by 82.1% with very practical categories.